Successful treatment of diffuse cutaneous leishmaniasis caused by Leishmania amazonensis, - Raimunda Nonata Ribeiro Sampaio; Marina Freitas Ferreira; Sofia Sales Martins; Jorgeth de Oliveira Carneiro da Motta (Sociedade Brasileira de Dermatologia, 2021)
Abstract Diffuse cutaneous leishmaniasis is a rare universal disease associated with an inadequate host cell immune response, caused by different species: infantum, aethiopica, major, mexicana, and others, which presents the challenge of a poor therapeutic response. In Brazil, it is caused by L. amazonensis. A case confirmed by histopathology with an abundance of vacuolated macrophages full of amastigotes and lymphocyte scarcity, identified by RFLP-ITS1PCR and in vitro decrease and exhaustion of the host cell immune response to L. amazonensis antigen, was treated early (3 months after the onset) with Glucantime (2 months) and allopurinol (29 months) with clinical cure, after a follow-up for 30 months after treatment.